VIRGINIA LAWS 1661-1676, at 37 (1676) (enacted 1665) - (:unkn) unknown (My University, 1665)
Enforced militias to arm themselves in order to protect churches, courts, and other public meetings from "Indians."
Keywords: ARMED FORCES